2000
DOI: 10.1177/002215540004800608
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 Gene Expression and Regulation in the Rodent Seminiferous Epithelium

Abstract: S U M M A R Y Connexin43 (Cx43) is one of the most predominant gap junction proteins found in the testis. We used in situ hybridization and indirect immunofluorescence to study the distribution of Cx43 mRNA and protein in the rodent seminiferous epithelium. During mouse testis maturation, Cx43 mRNA and its corresponding protein were first detected in the adluminal compartment of the growing seminiferous tubules (early postnatal age: Day 12) to become progressively located in the basal compartment at later ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 38 publications
15
110
0
3
Order By: Relevance
“…In the testis, ten Cx mRNAs are presumably translated within the seminiferous epithelium (Risley, 2000). We and others reported the presence of Cx43 in the basal compartment of seminiferous tubules in both Sertoli and germ cells (Risley et al, 1992;Pelletier, 1995;Batias et al, 2000) and its physiological implication in male fertility (Juneja et al, 1999;Plum et al, 2000;Defamie et al, 2001). More recently, we have characterized the presence of Cx43-based gap junctions between neighboring Sertoli cells, between Sertoli cells and spermatogonia and between Sertoli cells and spermatocytes (Decrouy et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the testis, ten Cx mRNAs are presumably translated within the seminiferous epithelium (Risley, 2000). We and others reported the presence of Cx43 in the basal compartment of seminiferous tubules in both Sertoli and germ cells (Risley et al, 1992;Pelletier, 1995;Batias et al, 2000) and its physiological implication in male fertility (Juneja et al, 1999;Plum et al, 2000;Defamie et al, 2001). More recently, we have characterized the presence of Cx43-based gap junctions between neighboring Sertoli cells, between Sertoli cells and spermatogonia and between Sertoli cells and spermatocytes (Decrouy et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The localization of Cx33 and Cx43 in cells or in testis sections was assessed as previously described (Batias et al, 2000;Defamie et al, 2001). Briefly, 5 µm testis sections or cells were fixed with cold methanol, permeabilized for 5 minutes with saponin buffer (0.5% saponin, 2.5% goat serum, 1% bovine serum albumin and 0.2% gelatin in PBS) and incubated overnight with Cx33, Cx43 and myc (1/100) antibodies at 4°C.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…There is also some evidence that peritubular myoid cells and endothelial cells of testicular blood vessels contribute to barrier function (Plöen & Setchell, 1992;Holash et al, 1993). As well as tight junctions, gap junctions are also present in the blood-testis barrier as shown by ultrastructural analysis in rats (Dym & Fawcett, 1970;Gilula et al, 1976;Batias et al, 2000). The blood-testis barrier sequesters germ cells usually considered antigenic, protecting the differentiated germ cells from the autoimmune response (Pelletier & Byers, 1992;Willing et al, 1998;Hemendinger et al, 2002) and from exposure to many compounds found in blood or interstitial tissue fluid which can be harmful to germ cells (Waites & Glawell, 1982;Bart et al, 2004;Augustine et al, 2005).…”
Section: Compartmentalization and The Blood-testis Barriermentioning
confidence: 99%
“…35 Among these 11 Cxs, Cx43, the most widely distributed Cx in the organism, is early expressed during development [36][37][38] and is the most predominant Cx in the growing testis. 39,40 Connexin localization in the testis. In fetal and newborn rats, and at the time of initiation of spermatogenesis, Cx43 is present between Leydig cells, between Sertoli cells and between Sertoli and germ cells.…”
Section: Connexin Expression Function and Regulation In The Developimentioning
confidence: 99%
“…2), which shifts from the apical to the basal regions of seminiferous tubules. 42,44,45 From postnatal day 12 and thereafter, Cx43 appears as an intense and focal band distributed close to the base of the seminiferous tubule (Fig. 2).…”
Section: Connexin Expression Function and Regulation In The Developimentioning
confidence: 99%